Predictive Value of the Platelet-to-Albumin Ratio (PAR) on the Risk of Death at Admission in Patients Suffering from Severe Fever with Thrombocytopenia Syndrome - Gui Y; Xu Y; Yang P (Dove Medical Press, 2021)
Yonghui Gui,1 Yuanhong Xu,2 Peng Yang1 1Department of Blood Transfusion, The First Affiliated Hospital of Anhui Medical University, Hefei, 230022, Anhui, People's Republic of China; 2Department of Clinical Laboratory, The First Affiliated Hospital of Anhui Medical University, Hefei, 230022, Anhui, People's Republic of ChinaCorrespondence: Peng YangDepartment of Blood Transfusion, The First Affiliated Hospital of Anhui Medical University, Hefei, 230022, Anhui, People's Republic of ChinaEmail yangpeng00812@163.comYuanhong XuDepartment of Clinical Laboratory, The First Affiliated Hospital of Anhui Medical University, Hefei, 230022, Anhui, People's Republic of ChinaEmail xyhong1964@163.comObjective: The purpose of this study was to evaluate the predictive value of the platelet-to-albumin ratio (PAR) on the risk of death in patients with severe fever with thrombocytopenia syndrome.Methods: Between Jan 2019 and June 2021, 127 cases which were admitted to the First Affiliated Hospital of Anhui Medical University have been included in this study. The laboratory data were selected at the time of admission. To identify the potential independent risk factors for severe fever associated with thrombocytopenia syndrome, multivariate logistic regression analysis was performed. Receiver operating characteristic (ROC) curve analysis was used to evaluate the prediction accuracy of PAR in identifying patients exhibiting severe fever with thrombocytopenia syndrome.Results: Multiple logistic regression analysis showed that PAR could potentially serve as an independent risk factor for the death in patients with SFTS (OR = 4.023, 95% CI 1.204- 13.436, P=0.024). The prediction of the risk of death in patients with SFTS was assessed using the AUC. The AUC for the PAR was 0.729 (95% CI, 0.637- 0.82, P < 0.001), whereas the optimal cut-off value of PAR was found to be 1.43, with 54.9% sensitivity and 86.1% specificity.Conclusion: Our study demonstrated for the first time that PAR could act as an independent predictor for mortality in adult patients with SFTS.Keywords: severe fever with thrombocytopenia syndrome, risk factors, platelet-to-albumin ratio